Políticas públicas e associativismo no RN: experiências populares - Melo, Célia Regina Silva Stocco de (2007)
Rural Popular experiences, socially organized on the constructions of the dams at Espinharas River, Serra Negra do Norte, which have been investigated, have reached in positive results. Several institutions, such as the City and State Power, multilaterals, governmental and non-governmental financial organizations, commonly refer to the success of such experiences. What success are they referring to? Is it recognized by family rural workers? What about institutional parts, how do they evaluate such experience? Is there legal continuity on such association structure? What kinds of gains have there been with such experiences? Has the association structure become any stronger? In search for demystifying the process, it has been made a research on classic and contemporaneous authors, as well as the interview of ten institutional parts, and twenty rural parts involved on the process, as well as the analysis of thirty-eight of the associations. It was concluded that the applied social public policies had resulted in heterogeneous social-economical process that has fulfilled the first step of a planning (not yet documented, but know by some institutional parts which lead, and still lead such social initiative). In the coming years the associations are to have a great potential for development, with the dams, as well as other projects. This persistence and external support, when integrated may have great deeds come to reality